Megafaunal split ends: microscopical characterisation of hair structure and function in extinct woolly mammoth and woolly rhino - Tridico, Silvana; Rigby, P.; Kirkbride, K.; Haile, James; Bunce, Michael (Pergamon, 2014)
The large extinct megafaunal species of the Late Pleistocene, Mammuthus primigenius (woolly mammoth) and Coelodonta antiquitatis (woolly rhino) are renowned for their pelage. Despite this, very little research has been conducted on the form and function of hair from these iconic species. Using permafrost preserved hair samples from seven extinct megafaunal remains, this study presents an in-depth microscopical characterisation of preservation, taphonomy, microbial damage, pigmentation and morphological features of more than 420 hairs. The presence of unique structural features in hairs, from two extinct megafauna species, such as multiple medullae and unparallelled stiffness suggests evolution of traits that may have been critical for their survival in the harsh arctic environment. Lastly, despite popular depictions of red-haired and/or uniformly coloured mammoths, a closer examination of pigmentation reveals that mammoth coats may have exhibited a mottled/variegated appearance and that their ‘true’ colours were not the vivid red/orange colour often depicted in reconstructions. Insights gained from microscopical examination of hundreds of extinct megafauna hairs demonstrate the value of extracting as much morphological data as possible from ancient hairs prior to destructive sampling for molecular analyses.